"Mother-Warriors": Queer Motherhood as Resistance in Arundhati Roy's The Ministry of Utmost Happiness. Issue 3 (3rd July 2021) - Kuiti, Samadrita
Abstract: This article examines the motifs of queer motherhood and womanhood in Arundhati Roy's novel The Ministry of Utmost Happiness as strategies of resistance against an increasingly totalitarian Indian state, particularly in light of the resurgence of Hindutva extremism and state-sanctioned repression of sexual, gender, caste, and religion-based minorities. Drawing on scholarship from queer theory, South Asian, and motherhood studies, and their underemphasized intersections, I interpret the novel's recalibration of adoptive adult-female/female-child relationships as a legitimate queer feminist praxis that, in turn, signals ahead to a utopian future that will pose an ideological challenge to the heteropatriarchal institutions of a nation currently experiencing the detrimental impacts of global capitalism and neoliberalism. I go on to contend that Roy's portrayal of the two female protagonists and their queered relationship to two abandoned girl children, whom they adopt and care for without the sanction of social and legal systems, is a direct critique of the devaluation of the lives of South Asian girl children and a violation of the norms of compulsory heteronormativity. Lastly, I supplement my reading of queer motherhood in the novel with analysis of both mainstream and academic discourses on real hijra mother-adoptive daughter relationships.